The I/O-Complexity of Ordered Binary-Decision Diagram Manipulation - Arge, Lars (BRICS Report Series, 1996)
Ordered Binary-Decision Diagrams (OBDD) are the state-of-the art data structure for boolean function manipulation and there exist several software packages for OBDD manipulation. OBDDs have been successfully used to solve problems in e.g. digital-systems design, verification and testing, in mathematical logic, concurrent system design and in artificial intelligence. The OBDDs used in many of these applications quickly get larger than the available main memory and it becomes essential to consider the problem of minimizing the Input/Output (I/O) communication. In this paper we analyze why existing OBDD manipulation algorithms perform poorly in an I/O environment and develop new I/O-efficient algorithms.